Variability of the env gene in cynomolgus macaques persistently infected with human immunodeficiency virus type 2 strain ben. - Tolle, T (1994)
The sequence variability of distinct regions of the proviral env gene of human immunodeficiency virus type 2 strain ben (HIV-2ben) isolated sequentially over 3 to 4 years from six experimentally infected macaques was studied. The regions investigated were homologous to the V1, V2, V3, V4, V5, and V7 hypervariable regions identified in the env genes of HIV-1 and simian immunodeficiency virus SIVmac, respectively. In contrast to findings with HIV-1 and SIVmac, the V1- and V2-homologous regions were found to be highly conserved during the course of the HIV-2ben infection in macaques. The V3-homologous region showed a degree of variation comparable to that of HIV-1 but not of SIV. In the V4-, V5-, and V7-homologous regions, mutation hot spots were detected in most reisolates of the infected monkeys. Most of these mutations occurred during the first 10 weeks after infection. After 50 weeks, new mutations were rarely detected. At most mutation sites, a dynamic equilibrium between the mutated viral isotype and the infecting predominant wild type was present. This equilibrium might prevent an accumulation of mutations in isolates later in the course of infection.